Design of a Hybrid Fiber Optic Daylighting and PV Solar Lighting System. (July 2018) - Lv, Yuexia; Xia, Longyu; Yan, Jinyue; Bi, Jinpeng
Abstract: Residential buildings with limited natural lighting are generally lit by fuel-based electricity which contributes to increase of CO2 concentration in the atmosphere. This paper presents the design of a hybrid fiber-optic daylighting and PV solar lighting system for household applications. The system is composed of a light collecting subsystem, a light guiding subsystem, an optical fiber light diffuser subsystem and corresponding control system. Preliminary system performance shows that, the developed system could provide comfortable and natural indoor illumination. Meanwhile, the hybrid lighting system can provide an average of 9h of electric lighting under clear sky conditions, and reduce 158.2kg of carbon dioxide emission in a year within the tested dark room of 5m 2 .